Development and evaluation of ginger-honey shrikhand – a fermented sweet delicacy - Viren Savaliya; Ahuja, Kunal Kumar; Thesiya, Ankitkumar J.; Hazra, Tanmay (Indian Journal of Dairy Science, 2023)
Shrikhand is a semi-soft, pleasant sweetish-sour, whole milk fermented product popular in the western parts of the India and is prepared by mixing chakka with sugar, cream and other ingredients. Levels of milk fat content, sugar: honey ratio (partial replacement) and ginger juice concentration was optimized using central composite rotatable design of response surface methodology. Optimized formulation of ginger-honey shrikhand contained 3.16% milk fat content, 79.61 sugar: honey ratio and 3.79% ginger juice concentration (on chakka basis) and gave an overall acceptability score of 8.07 ± 0.06 on a 9-point hedonic scale. Ginger-honey shrikhand samples packed in polystyrene cups remained acceptable on 30th day of storage at 7 ± 1°C with OAS of 7.83 ± 0.06. Responses from 90 consumers indicated wide acceptability of ginger-honey shrikhand among consumers with average overall liking score of 8.25 on 9-point hedonic scale.